Population dynamics of the geographically defined metapopulations of brown shrimp Metapenaeus monoceros (Fabricius, 1798) from Indian waters - A. P. Dineshbabu; P. T. Sarada; G. Maheswarudu; Pillai, S. Lakshmi; Dash, Gyanranjan; Divipala, Indira; Kumar, Rajan; Chakraborty, Rekha Devi; M. Rajkumar; J. Jayasankar; R. Ratheeshkumar; K. N. Saleela; et al. (Indian Journal of Fisheries, 2022)
Population dynamics of the brown shrimp Metapenaeus monoceros (Fabricius, 1798) was studied along the Indian coast using catch and effort data of trawlers from 8 States and 2 Union Territories for the period 2007-2015. Classical length-based stock assessment methods and spatial database of the shrimp catch were used to derive fishing ground related conclusions. Inclusion of spatial data revealed the possibility of existence of metapopulations of M. monoceros in the region. Maximum sustainable yield (MSY) cannot be a reasonable reference point for deciding the fishing pressure in M. monoceros. By analysing stock fluctuations noticed during the study period with varying spawning stock biomass combinations, retention of 40% spawning biomass seems to be a safe option for sustaining M. monoceros production from Indian waters. Based on this, the study recommends reduction of fishing pressure along north-west, south-west and northeast coast by 70, 60 and 70% respectively from the base level of effort in 2017. The study illustrates that the spatial data from fishing ground, can serve as an additional tool to derive management options. The study also emphasises the need for further investigations on the possibilities of metapopulations of M. monoceros which is widely distributed in all agro-climatic zones along the Indian coast. Keywords: Indian coast, Metapopulation, M. monoceros, Spatial study, Stock assessment